Analisis Teologi Lingkungan Seyyed Hossein Nasr Terhadap Krisis Air di Masyarakat Batujaya Karawang - Fradiv Mochammad Sulthan Rafly; Muhlas Muhlas; Munir Munir (Jurnal Riset Agama, 2022)
Disposal of trade waste and household waste has negative impacts, such as land shifts, floods, air pollution, and other disasters. The same thing happened in Batujaya, precisely in the hamlet of South Bakung, where the river is the most practical place for disposing of waste. The purpose of this paper is to describe the research points: 1). How is the water crisis as a form of environmental damage in the people of Batujaya Karawang; 2). How does Seyyed Hossein Nasr's analysis of environmental theology view the water crisis as environmental damage. This research is a direct field research, using qualitative descriptive method, and Seyyed Hosein Nasr's theory of environmental theology as the analytical knife. The results of this study found that first, the people of Batujaya, especially the South Bakung community, were in danger of throwing garbage into the river. Second, the lack of anticipation from the government and the sanctions given to the people of Batujaya, especially in South Bakung, for the disposal of trade waste and household waste into the river. Third, make people in Batujaya, especially in South Bakung aware, not to throw garbage into the river anymore by means of physical and spiritual socialization.